Kinesiophobia, fear of fall, neuropathic pain and navicular drop in rheumatoid arthritis- a correlation study - Phadke, Shiwani; Puntambekar, Anjali; Gill, Niharika (International Journal Of Community Medicine And Public Health, 2021)
Background: Rheumatoid arthritis (RA) is one of the most common chronic health conditions and a leading cause of pain; joint damage and disability. Fear of fall and kinesiophobia are associated with activity limitations in RA patients because of pain and stiffness which affects the quality of life. Kinesiophobia and fear of fall are associated with pain. The pathogenics and chronicity of RA can lead to neuropathic pain. Hence the aim of this study was to assess pronation of foot and evaluate if there is any correlation between fear of fall, kinesiophobia and neuropathic pain in patients with rheumatoid arthritis. Methods: Subjects in the age group of 30-50 years were included after passing the EULAR criteria and were assessed for navicular drop by using the navicular drop test. Later they were assessed for fear of fall, kinesiophobia and neuropathic pain using fall efficacy scale, Tampa scale and LANSS questionnaire respectively. Results: Significant co-relation was found between kinesiophobia and fear of fall (p value =0.0046) and there were non-significant co-relations between all other factors. Conclusions: Participants with RA showed significant navicular drop where left subtalar joint was more affected than right. According to the LANSS score subjects showed lower concerns of neuropathic pain. Maximum number of subjects displayed high concerns of kinesiophobia and fear fall which proves the significant association between the factors.